Loop flexibility in human telomeric quadruplex small-molecule complexes. Issue 10 (4th May 2015) - Collie, Gavin W.; Campbell, Nancy H.; Neidle, Stephen
Abstract: Quadruplex nucleic acids can be formed at the ends of eukaryotic chromosomes. Their formation and stabilisation by appropriate small molecules can be used as a means of inhibiting the telomere maintenance functions of telomerase in human cancer cells. The crystal structures have been determined for a number of complexes between these small molecules and human telomeric DNA and RNA quadruplexes. The detailed structural characteristics of these complexes have been surveyed here and the variations in conformation for the TTA and UUA loops have been explored. Loop conformations have been classified in terms of a number of discrete types and their distribution among the crystal structures. Sugar conformation and backbone angles have also been examined and trends highlighted. One particular loop class has been found to be most prevalent. Implications for in particular, rational drug design, are discussed.